(untitled) (PerCursos, 2021)
This article aims to invite for a reflection on the colonization processes suffered by the indigenous peoples of Latin America, in particular, the Guarani. The article is characterized as a research of theoretical-epistemological character, and of literature review. We chose the interculture as an epistemological perspective (CANCLINI, 2006) for the construction of a dialogue where cultures don’t overlap one another, but rather dialogue with each other aiming to build new ways of thinking the cultural relations as intercultural processes. We propose a knowledge that privileges the contact between the local and the global culture (GEERTZ, 2009) without having as its orientation the hierarchy of the ways of understanding, doing and promoting the relations between the different cultures that intersect and intertwine. As a final reflection, we present the way/concept of living from the Guarani people, a mystical/religious concept of the “search of the Earth without Evil”. We assume that the search of the earth without evil transforms the way how Guarani Indians see the paths of daily life.